Growth and characterization of an epitaxially grown ZnSSe/MnZnSSe distributed Bragg reflector - HEGARTY, JOHN (My University, 1995)
A Bragg reflector consisting of a 25-period MnZnSSe/ZnSSE Bragg stack is reported. The II?VI semiconductor structure was grown by molecular beam epitaxy on a GaAs ~100! epilayer. Structural characterization of the Bragg reflector was performed with double crystal x-ray diffraction and transmission electron microscopy. These studies indicated that the epitaxial II?VI structure, whose total thickness is about 2150 nm, remains pseudomorphic with the GaAs substrate. The Bragg stack has a maximum reflectance of 81% at 468 nm. This result shows that fabrication of high reflectance mirrors from epitaxial ZnSe-based II?VI compounds is possible in spite of relatively small refractive index differences between constituent II?VI layers.
PUBLISHED
Keywords: Physics